2005
DOI: 10.1529/biophysj.105.063040
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Antimicrobial Peptide Cyclo(RRWWRF) with Membranes by Molecular Dynamics Simulations

Abstract: Antimicrobial peptides have gained a lot of interest in recent years due to their potential use as a new generation of antibiotics. It is believed that this type of relatively short, amphipathic, cationic peptide targets the bacterial membrane, and destroys the chemical gradients over the membrane via formation of stable or transient pores. Here we use the NMR structure of cyclo(RRWWRF) in a series of molecular dynamics simulations in membranes at various peptide/lipid ratios. We observe that the NMR structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
39
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 45 publications
(58 reference statements)
5
39
0
Order By: Relevance
“…A more detailed description of a possible mode of action based on a molecular dynamics study of c-RW embedded in a lipid bilayer will be published. [25] In conclusion we have shown that c-RW undergoes a conformational change upon membrane binding. This results in an altered structure that is induced by the lipid environment, irrespective of the charge.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…A more detailed description of a possible mode of action based on a molecular dynamics study of c-RW embedded in a lipid bilayer will be published. [25] In conclusion we have shown that c-RW undergoes a conformational change upon membrane binding. This results in an altered structure that is induced by the lipid environment, irrespective of the charge.…”
Section: Discussionmentioning
confidence: 63%
“…[27] However, backbone cyclization restricts the maximum possible length of peptide to about 25 , from the tip of the R2 side chain to that of the R5. If the hydrophobic core of the membrane were lined by the cluster of aromatic residues, which are only about 16 in length, this would result in a considerable hydrophobic mismatch with the membrane, which has a hydrophobic core of approximately 25-30 . Since such an arrangement would be highly unfavoura- ble, [25] it appears that this model cannot be used for the interpretation of the presented results; even though it seems to explain the effect of other helical peptides. Also, for other peptides that could potentially span the membrane in a barrel-stave-like fashion, cyclization makes membrane spanning unlikely without destroying their activity.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The peptide backbone lies parallel to the lipid bilayer surface, the positively charged R residues interact with the phosphate groups of the lipids, and aromatic residues insert into the membrane (7). Lipid demixing and domain formation in 1,2-dipalmitoyl-sn-glycero-3-[phospho-rac-(1-glycerol)]-1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine bilayers have been suggested as the basis for the selective antibacterial action of c-RW (8).…”
mentioning
confidence: 99%
“…We have recently determined the structure of the antimicrobial peptide cyclo-(Arg-Arg-Trp-Trp-ArgPhe) (c-RW) and several analogues using solution NMR spectroscopy and have described their potential interactions with a biological membrane using extensive molecular dynamic simulations [6,7]. The membranemimicking environment, in our case DPC micelles, leads to a change in the structure of the peptides as compared to their conformation in aqueous solution.…”
mentioning
confidence: 99%